Vì \(\frac{a+2007}{a-2007}=\frac{b+2008}{b-2008}\)
Suy ra: \(\frac{a+2007}{b+2008}=\frac{a-2007}{b-2008}\)
Theo tính chất dãy tỉ số bằng nhau thì:
\(\frac{a+2007}{b+2008}=\frac{a-2007}{b-2008}=\frac{\left(a+2007\right)+\left(a-2007\right)}{\left(b+2008\right)+\left(b-2008\right)}=\frac{\left(a+2007\right)-\left(a-2007\right)}{\left(b+2008\right)-\left(b-2008\right)}\)
Lấy 2 phân số cuối cùng của dãy tỉ số trên và rút gọn ta được:
\(\frac{2a}{2b}=\frac{2.2007}{2.2008}\)
\(\Rightarrow\frac{a}{b}=\frac{2007}{2008}\)
Ta có:
\(\frac{a+2017}{a-2017}=\frac{b+2018}{b-2018}\)
=>\(\frac{a+2017}{b+2018}=\frac{a-2017}{b-2018}\)
=>\(\frac{a}{b}=\frac{2017}{2018}\)
=>\(\frac{a}{2017}=\frac{b}{2018}\)
Vậy nếu \(\frac{a+2017}{a-2017}=\frac{b+2018}{b-2018}\)thì \(\frac{a}{2017}=\frac{b}{2018}\)